HUBUNGAN PEMBERIAN INSENTIF NON MATERIAL OLEH PIMPINAN DENGAN SEMANGAT KERJA PEGAWAI PADA DINAS PENDIDIKAN KOTA SOLOK - Ferdino Wedi Sanjaya (Jurnal Bahana Manajemen Pendidikan, 2014)
This type of research is descriptive and correlational research. The population is all employees of the Department of Education Solok as many as 105 people. Samples taken are as many as 86 people were determined through Simple Random Sampling technique to look at the table Krecjie-Morgan. Scale model ofthe research instrument is Likert kuisnioner tested the validity and reliable. Datawere analyzed by using Product Moment Correlation. The results of the data analysis can show that: Non Material Incentives are in enough categories (71.3%) and employee morale in the category enough(79.5%). There is a significant and positive relationship between the Non Material Incentives By Leaders In Employee Morale In the Solok City Department of Educationwith acorrelation coefficientat 99% confidence levelwith rhitung = 0.700 > = 0.317 rtabel. From the above resultsit can be concluded that the non material incentives, is one of the factors that affect employee morale. Keyword:Non MaterialIncentivesAndEmployee Morale